If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -3(x + -4) = 11 Reorder the terms: 2 + -3(-4 + x) = 11 2 + (-4 * -3 + x * -3) = 11 2 + (12 + -3x) = 11 Combine like terms: 2 + 12 = 14 14 + -3x = 11 Solving 14 + -3x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -3x = 11 + -14 Combine like terms: 14 + -14 = 0 0 + -3x = 11 + -14 -3x = 11 + -14 Combine like terms: 11 + -14 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 2+6h+18=2.4h+22 | | 98+12= | | x+9=2x-1 | | -5n-2+3(2n+1)=4n-3 | | 2a-3=25 | | 2p*3=12p*2 | | 8n=n-90 | | 10p+5=18p-6 | | 3+1+2-3m=9150 | | 4x+21123-14123=34180 | | a-9=59 | | 80x+2-2x=1 | | 5+3r=4r+2 | | 15+2g=3+5g | | 120000+12x=28x | | 6p-12=4p+18 | | 6x-16+4x+30=180 | | 3x-21=2x | | a-4bx=(a+x)(a+3y) | | 1664168=v | | -4(x+16)=-116 | | a+7=4 | | 14n+3n=8n-3(n-4) | | 6x-16+4x+30= | | 4n+1=12+6 | | 12*4-10/2=-16 | | 3x+25=33 | | 30=10x+15 | | 1-1=5(1)+3(1)-8 | | -5n+1=-9-5n+5n | | 5x+8x+2x=360 | | -(2x-3)+3x=-10 |